Analisis kemampuan siswa dalam menyelesaikan soal matematika tipe higher order thinking skill (hots) pada materi bangun ruang kelas V sekolah dasar - Winahyu, Ajeng Riska; Rukayah, Rukayah; Kurniawan, Sandra Bayu (Didaktika Dwija Indria, 2025)
The aim of this study is to find out how students are able to solve Higher Order Thinking Skill (HOTS) type problems. This study uses a descriptive qualitative research method. The subject of this study is 17 students in grade V of SD Negeri Sambi 1. The data collection techniques used are observation, interviews, and documentation studies. The validity test of the data was carried out using triangulation techniques. The analysis technique chosen is the interactive analysis technique from Miles and Huberman with. The results of the study were that 34% of students were able to solve the problem in the first step (understanding the problem), as many as 20% of students were able to solve the problem until the second step (planning the solution), as many as 27% of students were able to solve the problem until the third step (completing the plan), in the fourth step (checking the answer again) all students were not able to complete the steps well, as many as 19% of students were not able to work using the steps to solve the problem.